THE RELATIONSHIP BETWEEN NURSE CARING AND PATIENT FAMILY SATISFACTION IN THE IGD ROOM RSJD DR ARIF ZAINUDIN SURAKARTA - Sulistyaningsih, Sulistyaningsih; Agustin, Wahyu Rima; Suryandari, Dewi (Universitas Kusuma Husada Surakarta, 2025)
Caring is central to nursing practice because caring is a dynamic approach, where nurses work to further improve their care for patients. Patient satisfaction is an evaluation or assessment after using a service, that the chosen service at least meets or exceeds expectations. If the patient's family asks about the patient's illness then the nurse does not give an answer in accordance with the intention of the patient's family, it will cause anxiety and fear of the action procedures given to the patient. The purpose of this study is to determine whether there is a relationship between nurse caring and patient family satisfaction in the emergency room of Surakarta Mental Hospital. The criteria for respondents are the families of patients with patients who will be hospitalized at Dr. Arif Zainuddin Surakarta Hospital with a sample of 15 people. How to collect data is by giving a caring questionnaire and satisfaction questionnaire to the patient's family. The results obtained from the analysis with the Chi Square statistical test explained the results of asym sig. 0.001 (<0.05) and it can be concluded that there is a relationship between caring nurses and patient family satisfaction in the emergency room of Dr. Arif Zainudin Surakarta Hospital.